A giant exoplanet orbiting a very-low-mass star challenges planet formation models - Morales, Juan Carlos; Reffert, Sabine; Quirrenbach, Andreas; Kaminski, Adrian; Seifert, Walter; Kemmer, Jonas; Kim, Minjae; Klüter, Jonas; Labiche, Nicolas; Mandel, Holger; Sadegi, Sepideh; Stahl, Otmar; et al. (Science, 2019)
A small star hosts a big planet - M dwarfs, the most common type of star, are low-mass objects that emit most of their faint light in the near-infrared, making it difficult to detect any orbiting exoplanets. Morales et al. have observed the nearby M dwarf GJ 3512 in the optical and near-infrared (see the Perspective by Laughlin). Periodic variations in the star's radial velocity show that it hosts a gas giant exoplanet on an eccentric orbit. The authors use simulations to show that such a large exoplanet around such a small star has implications for models of planet formation. - Science, this issue p. 1441; see also p. 1382 - Surveys have shown that super-Earth and Neptune-mass exoplanets are more frequent than gas giants around low-mass stars, as predicted by the core accretion theory of planet formation. We report the discovery of a giant planet around the very-low-mass star GJ 3512, as determined by optical and near-infrared radial-velocity observations. The planet has a minimum mass of 0.46 Jupiter masses, very high for such a small host star, and an eccentric 204-day orbit. Dynamical models show that the high eccentricity is most likely due to planet-planet interactions. We use simulations to demonstrate that the GJ 3512 planetary system challenges generally accepted formation theories, and that it puts constraints on the planet accretion and migration rates. Disk instabilities may be more efficient in forming planets than previously thought. - A gas giant exoplanet orbits a low-mass star, a configuration that is difficult for planet formation models to reproduce. - A gas giant exoplanet orbits a low-mass star, a configuration that is difficult for planet formation models to reproduce.
Gesehen am 14.02.2020